2020
DOI: 10.1002/esp.4958
|View full text |Cite
|
Sign up to set email alerts
|

Rill network development on loessial hillslopes in China

Abstract: Rill network development not only potentially affects hillslope and drainage network evolution, but also causes severe soil degradation. However, the studies on rill network development remain inconclusive. This study aimed to investigate the temporal and spatial development of hillslope rill networks and their characteristics based on rainfall simulations and field observations. A soil pan (10.0m long × 3.0m wide × 0.5m deep) on a 20°slope was applied three successive simulated rains at two intensities of 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…7) is consistent with the findings of Fang et al (2015) and Tian et al (2020). However, Shen et al(2020) showed that the rill network mainly exhibits a dendritic pattern. The difference may be due to the fact that slope surface flow under scour conditions is surfaceproduced flow and is point-produced flow under rainfall conditions (Zhang et al, 2013), and the difference in the way they produce flow may lead to a different development of the rill network.…”
Section: Rill Network and Morphology Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…7) is consistent with the findings of Fang et al (2015) and Tian et al (2020). However, Shen et al(2020) showed that the rill network mainly exhibits a dendritic pattern. The difference may be due to the fact that slope surface flow under scour conditions is surfaceproduced flow and is point-produced flow under rainfall conditions (Zhang et al, 2013), and the difference in the way they produce flow may lead to a different development of the rill network.…”
Section: Rill Network and Morphology Characteristicssupporting
confidence: 88%
“…The parameters of rill erosion such as rill depth, rill width and width-to-depth ratio were selected to quantify the development characteristics of the rill network on the slope (Cerdan et al, 2002;Shen et al, 2020) and to reflect the intensity of rill erosion along the vertical and horizontal directions. Based on the 3D photo reconstruction technology Di Stefano et al, 2019), the photos taken by digital cameras were imported into Agisoft Photoscan Professional 1.2.4 (Agisoft LLC, St. Petersburg, Russia) for aligning photos, generating dense point clouds, generating grid textures, generating and exporting DEMs, and so on.…”
Section: Rill Morphology Parametersmentioning
confidence: 99%
“…Rill width, depth, width/depth ratio, density, and degree of dissection (Shen et al, 2020) were selected to assess rill morphology. The rill width (cm) and depth (cm) were computed using the mean values of the total measuring points of each rill.…”
Section: Methodsmentioning
confidence: 99%
“…Rill width, depth, width/depth ratio, density, and degree of dissection (Shen et al, 2020) were selected to assess rill morphology.…”
Section: Rill Morphological Characteristicsmentioning
confidence: 99%
“…The parameters of rill erosion such as rill depth, rill width and width-to-depth ratio were selected to quantify the development characteristics of the rill network on the slope (Cerdan et al, 2002;Shen et al, 2020) and to reflect the intensity of rill erosion along the vertical and horizontal directions. Based on the 3D photo reconstruction technology Di Stefano et al, 2019), the photos taken by digital cameras were imported into Agisoft Photoscan Professional 1.2.4 (Agisoft LLC, St. Petersburg, Russia)…”
Section: Rill Morphology Parametersmentioning
confidence: 99%